A high-efficiency and eco-friendly design for coal-fired power plants: Combined waste heat recovery and electron beam irradiation. (1st November 2022) - Xie, Shutao; Qin, Peijia; Zhang, Mingliang; Xu, Jisong; Ouyang, Tiancheng
Abstract: To ensure the sustainable development of the economy and society, energy-saving and emission reduction is an inevitable choice to solve resource scarcity and control environmental pollution, while coal-fired power plants are an important industry to implement this strategy. A novel design combining organic Rankine cycle with electron beam flue gas treatment is proposed to reduce pollutant emissions and recover flue gas waste heat of 600 MW power plant. The flue gas flows through the organic Rankine cycle to recover waste heat, then enters the electron beam irradiation device for desulfurization-denitrification, and eventually generates by-products of ammonium sulfate and ammonium nitrate that could be applied in agriculture. The particle swarm optimization algorithm is employed to improve the thermodynamic, economic and environmental performance, then the most suitable scheme is selected by combining TOPSIS and the entropy weight method. The optimization results indicate that the integrated system could produce equivalent electric quantity of 22.58 MW, and the payback period is 4.91 years. Meanwhile, ammonium sulfate and nitrate with production of 3544 kg/h and 6165 kg/h are obtained. Compared with the referenced power plant, the thermal efficiency of the improved scheme increases by 1.26% and the standard coal consumption rate decreases by 2.72%. Graphical abstract: Image 1 Highlights: A new integration of waste heat reuse and desulfurization-denitrification is proposed. The reaction mechanism and thermodynamic model of EBFGT are studied. TOPSIS and EWM are combined to screen the multi-objective functions optimized by PSO. The feasibility of system is discussed from thermodynamics, economy and environment.